Effects of experimental N addition on plant diversity in an old‐growth temperate forest. Issue 11 (2nd May 2018) - Lai, Mengying; He, Shanchuan; Yu, Shuang; Jin, Guangze
Abstract: Temperate forest ecosystems have experienced mounting negative effects due to increasing levels of nitrogen (N) deposition. We examined the effects of experimental N addition on plant diversity in an old‐growth temperate forest to test the following hypothesis: Long‐term excessive N addition decreases plant diversity by affecting the growth of plants, which results from changes in the soil nutrient content and a decrease in the soil pH in temperate forests. Experimental N additions were administered at the following levels since 2008: control (0 kg N ha −1 year −1 ), low N (30 kg N ha −1 year −1 ), medium N (60 kg N ha −1 year −1 ), and high N (120 kg N ha −1 year −1 ). Additionally, plant diversity was studied from 2014 to 2016. The results showed that the experimental N additions had significant effects on plant diversity and soil properties in an old‐growth temperate forest. The high‐N treatment decreased the density, cover, and diversity of understory plants, and some herbs even appeared to undergo premature aging, whereas the species diversity of herbs and ferns in the low‐N treatment plots showed a slight increasing tendency. This may have been because the old‐growth temperate forest is an N‐limited ecosystem, so the moderate N input did not show a large influence on plant diversity. However, the long‐term high‐N treatment ultimately reduced plant diversity by changing the soil nutrient contents, decreasing the pH values, and damaging plant growth. Our results suggested that the long‐term excessive N addition negatively affected the forest ecosystem in an N‐limited temperature forest. Abstract : We studied the interannual and seasonal responses of plant diversity to N addition in mixed broadleaved‐Korean pine forest of northeastern China and analyzed the reasons related to soil properties of diversity changes. We found that the long‐term excessive N addition caused a negative effect on the forest ecosystem in an N‐limited temperature forest.